2009
DOI: 10.1128/jcm.02040-08
|View full text |Cite
|
Sign up to set email alerts
|

Cholera Outbreaks Caused by an Altered Vibrio cholerae O1 El Tor Biotype Strain Producing Classical Cholera Toxin B in Vietnam in 2007 to 2008

Abstract: Vibrio cholerae O1 isolates collected during cholera outbreaks occurring from late 2007 to early 2008 in northern Vietnam were revealed to represent an altered strain containing the RS1 element followed by a CTX prophage harboring El Tor type rstR and classical ctxB on the large chromosome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 13 publications
2
108
0
2
Order By: Relevance
“…A few V. cholerae O1 ET carrying a tandem repeat of the CL CTX prophage on the small chromosome, indistinguishable from the Mozambique ET variant, were isolated in Vietnam between 1995(Nguyen et al, 2009. In a subsequent study, Tran et al (2012) showed that V. cholerae O1 ET involved in recurrent cholera in Vietnam (2007Vietnam ( -2010 was an ET variant carrying ctxB CL and rstR ET genes, as observed for ET strains involved in recurrent cholera in Khon Kaen, Thailand.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A few V. cholerae O1 ET carrying a tandem repeat of the CL CTX prophage on the small chromosome, indistinguishable from the Mozambique ET variant, were isolated in Vietnam between 1995(Nguyen et al, 2009. In a subsequent study, Tran et al (2012) showed that V. cholerae O1 ET involved in recurrent cholera in Vietnam (2007Vietnam ( -2010 was an ET variant carrying ctxB CL and rstR ET genes, as observed for ET strains involved in recurrent cholera in Khon Kaen, Thailand.…”
Section: Discussionmentioning
confidence: 98%
“…In a subsequent study, Tran et al (2012) showed that V. cholerae O1 ET involved in recurrent cholera in Vietnam (2007Vietnam ( -2010 was an ET variant carrying ctxB CL and rstR ET genes, as observed for ET strains involved in recurrent cholera in Khon Kaen, Thailand. Although the source of V. cholerae O1 ET analogous to the Mozambique variant of ET causing outbreaks in Thailand between 2003 and 2007 is not known, the Vietnamese ET strains carrying a tandem repeat of the CL CTX prophage and not involved in any major cholera outbreak were proposed to have been recently introduced into Vietnam (Nguyen et al, 2009). Our observations of temporal fluctuation in resistance to antimicrobial agents and a genetic transition from Mozambique variant type ET to Asian altered ET suggest that V. cholerae has a natural reservoir (niche), which has allowed the bacterium to evolve locally in Khon Kaen, although the appearance of the V. cholerae O1 altered ET carrying ctxB CL and rstR ET alleles has been hypothesized to be a recent event in Thailand (Okada et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Group I represents atypical El Tor strains with a tandem repeat of classical CTX prophage on the small chromosome, while Group II represents those possessing the RS1 and CTX prophage with El Tor type rstR and classical ctxB on the large chromosome. Based on these criteria, the Matlab and Mozambique variants were classified into Group I, while altered El Tor, such as those described by Nguyen et al (2009), fell into Group II. This classification system was also used by Goel et al (2011) to categorize the VCH35 isolate from Hyderabad, India into Group I, because it carried a tandem repeat of CTX prophage on the small chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis of CTX prophage array was performed using several combinations of primer pairs, as described by Nguyen et al (2009). The presence of a RS1 element was determined using the primer pair rstCF/rstCR.…”
Section: Genetic Analysis Of Ctx Prophage Arraymentioning
confidence: 99%
“…Since 2007, there have been several reports of cholera outbreaks or endemic cases caused by wave 3 strains in Southeast Asia (Ang et al, 2010;Okada et al, 2010;Choi et al, 2010). In Vietnam, about 20 000 cases were reported in 1964 at the beginning of the seventh pandemic of cholera; the early 1990s saw around 5000 cases per annum of cholera caused by V. cholerae O139; and in 2007, there was a large outbreak in northern Vietnam involving 1880 cases (World Health Organization, 2008) that were presumably caused by wave 3 strains (Nguyen et al, 2009;Choi et al, 2010) MLVA is a discriminatory and useful molecular epidemiological tool for studying the genetic relatedness of bacterial isolates based on the variability of VNTRs at multiple loci; the method has advantages for assessing short-term transmission of bacterial infectious diseases such as cholera (Choi et al, 2010;Moore et al, 2015). Our findings can aid in the surveillance of cholera in Vietnam and other countries where the disease is endemic.…”
Section: Introductionmentioning
confidence: 99%